2010
DOI: 10.1111/j.1439-0396.2009.00937.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: The approach to the mechanism of calcitonin gene-related peptide-inducing inhibition of food intake

Abstract: The aim of this study was to investigate the anorectic mechanism of calcitonin gene-related peptide (CGRP) in rats. Intraperitoneal injection of CGRP (50 μg/kg) resulted in decline (p < 0.05) in the food intake of rats at 0.5, 1, 2 and 4 h in comparison with saline control. Compared with saline-treated group, the levels of hypothalamic 3',5'-cyclic adenosine monophosphate (cAMP) and plasma glucagon were increased (p < 0.05) in CGRP-treated group, but insulin level was decreased (p < 0.05). No significant chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…It has been suggested that CGRP reduces food intake by means of suppressing orexigenic neuropeptides and/or stimulating anorexigenic neuropeptides expression in the hypothalamus (Sun et al, 2010). CGRP downregulated neuropeptide Y mRNA levels, but up regulated colecistokinin mRNA expression (Sun et al, 2010). These data suggest that the CGRP could be involved in the food intake response in the alpaca.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been suggested that CGRP reduces food intake by means of suppressing orexigenic neuropeptides and/or stimulating anorexigenic neuropeptides expression in the hypothalamus (Sun et al, 2010). CGRP downregulated neuropeptide Y mRNA levels, but up regulated colecistokinin mRNA expression (Sun et al, 2010). These data suggest that the CGRP could be involved in the food intake response in the alpaca.…”
Section: Discussionmentioning
confidence: 92%
“…It has been demonstrated that the anorectic effect exerted by the CGRP is specific, since the peptide decreases food intake without causing overt signs of discomfort or malaise and without inducing a conditioned taste aversion (Morley et al, 1996). It has been suggested that CGRP reduces food intake by means of suppressing orexigenic neuropeptides and/or stimulating anorexigenic neuropeptides expression in the hypothalamus (Sun et al, 2010). CGRP downregulated neuropeptide Y mRNA levels, but up regulated colecistokinin mRNA expression (Sun et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…The direct activation of GPCRs expressed in sensory afferent neuronal fibers within lymphatic vessels by lymphatic fluid allows the intestinal contents and interstitial paracrine agents to act like hormones. Additionally, given the anorectic effects of central and circulating sensory neuropeptides such as CGRP (64), our data point to a new pathway for the modulation of behavior, such as food intake, by premetabolized dietary nutrients via MLF-GPCR activation of sensory nerves, which represents a neurolymphocrine system (Fig. 8).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that intraperitoneal injection of CGRP increases plasma CGRP-levels and causes a loss of appetite in rats (Sun et al, 2010). Despite gavage with SH also increasing plasma CGRP-levels, this increment (of around 70%) was much lower than that obtained by intra peritoneal injection (of around 530%), and did not exert an anorectic effect, even after 24 h of food deprivation.…”
Section: Discussionmentioning
confidence: 93%
“…CGRP is known as one of the most potent arterial and venous vasodilators (Gupta et al, 2006), with potency 10-fold greater than the prostaglandins and up to 1000 times greater than the other classic vasodilators (Brain & Grant, 2004). The capacity of CGRP to regulate the development of T cells (Bulloch, McEwen, Nordberg, Diwa, & Baird, 1998), to induce satiety (Sun, Jing, Wang, & Weng, 2010), and its ability to exert gastric acid protection (Lenz, Mortrud, Vale, Rivier, & Brown, 1984) have also been documented. Recently, the important role of a-CGRP in the local regulation of bone metabolism has been reported 1756-4646/$ -see front matter Ó 2012 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 96%